2020
DOI: 10.1093/ibd/izaa009
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Noncoding RNAs in Pediatric Inflammatory Bowel Disease

Abstract: Prevalence of inflammatory bowel disease (IBD), a chronic inflammatory disorder of the gut, has been on the rise in recent years—not only in the adult population but also especially in pediatric patients. Despite the absence of curative treatments, current therapeutic options are able to achieve long-term remission in a significant proportion of cases. To this end, however, there is a need for biomarkers enabling accurate diagnosis, prognosis, and prediction of response to therapies to facilitate a more indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…Studies performed on cohorts of pediatric patients are rather sparse and of limited reliability, as most of the studies work with several dozen patients at most. Despite all the limitations, the results are mutually confirming [ 12 ], at least in the cases of several miRNAs, namely miR-21, miR-146a and miR-142-3p [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Studies performed on cohorts of pediatric patients are rather sparse and of limited reliability, as most of the studies work with several dozen patients at most. Despite all the limitations, the results are mutually confirming [ 12 ], at least in the cases of several miRNAs, namely miR-21, miR-146a and miR-142-3p [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 64%
“…A reasonable number of candidate miRNAs were selected based on a literature review published elsewhere [ 12 ]. These were only demonstrably dysregulated miRNAs in terms of downregulation and upregulation in pediatric patients: 5 upregulated (miR-21-5p, miR-142-3p, miR-146a-5p, miR-223-3p and let-7i-5p) and 5 downregulated (miR-192-5p, miR-194-5p, miR-200b-3p, miR-375-3p and miR-4284).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNAs act as powerful regulators of gene expression, mostly via interacting with the 3 UTR of target mRNAs, which inhibit translation or induces mRNA degradation [14]. Additionally, they can also bind to 5'UTR of target mRNAs or bind to coding sequence regions [15]. A number of studies have revealed that miRNAs are involved in the regulation of cell homeostasis by controlling important cellular processes including the development, differentiation, proliferation, apoptosis and stress reaction.…”
Section: Introductionmentioning
confidence: 99%